Learning a Language from Inconsistent Input: Regularization in Child and Adult Learners. Issue 3 (3rd July 2022) - Austin, Alison C.; Schuler, Kathryn D.; Furlong, Sarah; Newport, Elissa L.
ABSTRACT: When linguistic input contains inconsistent use of grammatical forms, children produce these forms more consistently, a process called " regularization ." Deaf children learning American Sign Language from parents who are non-native users of the language regularize their parents' inconsistent usages. In studies of artificial languages containing inconsistently used morphemes, children, but not adults, regularized these forms. However, little is known about the precise circumstances in which such regularization occurs. In three experiments we investigate how the type of input variation and the age of learners affects regularization. Overall our results suggest that while adults tend to reproduce the inconsistencies found in their input, young children introduce regularity: they learn varying forms whose occurrence is conditioned and systematic, but they alter inconsistent variation to be more regular. Older children perform more like adults, suggesting that regularization changes with maturation and cognitive capacities.